Implementasi Qisas dan Diyat dalam Sistem Hukum Pidana Indonesia: Analisis Normatif Terhadap Kompatibilitas Syariat Islam dengan Hukum Positif - Muh Ihkhsan; Kurniati K; Musyfikah Ilyas (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The transformation of Indonesian criminal law through Law Number 1 of 2023 opens opportunities for integrating Islamic sharia values within the national legal pluralism framework. This research examines the compatibility of qisas and diyat concepts with Indonesia's positive punishment system through a normative juridical approach analyzing philosophical convergence, juridical legitimacy, and sociological acceptability. Qisas as proportional retributive sanction and diyat as financial compensation represent a restorative justice paradigm aligned with contemporary punishment theories. Analysis of Articles 2, 51-52, and 96-97 of the new Criminal Code demonstrates that national legislation has accommodated living law in society, including religious values, as the basis for criminal case resolution. Philosophical convergence is identified through alignment between maqasid al-shariah (al-zajr, al-tashfiyah, al-islah) and national punishment objectives emphasizing preventive, rehabilitative, and restorative aspects. Juridical legitimacy is strengthened by the implementation experience of qanun jinayat in Aceh Province based on Law Number 11 of 2006 concerning Aceh Governance. The recommended implementation model encompasses diversion and restorative justice mechanisms for case resolution through penal mediation, formal application in autonomous regions, and integration of diyat as alternative sanction with judicial discretion